Penataan dan Pemanfaatan Sarana Prasarana Pembelajaran Pendidikan Formal dan Nonformal - Ayu Anindya Rasyad; Nurul Ulfatin; Agus Timan; Ayu Anindya Rasyad; Nurul Ulfatin (Universitas Negeri Malang, 2023)
Abstract: This study aims to identify and describe the arrangement and utilization of learning infrastructure for formal and non-formal education. This research uses qualitative methods with the type of case study research. The research data which was conducted at Pondok Pesantren An-Nur II Malang was collected using interview, observation, and documentation techniques. Then analyzed through an interactive process through the stages of data reduction, presentation, and verification. The results of this study are: (1) the types of infrastructure at the An-Nur II Malang Islamic Boarding School, (2) the arrangement of the infrastructure facilities at the An-Nur II Islamic Boarding School Malang; (a) the principles of structuring educational facilities and infrastructure include the relationship between spaces, land area, spatial framework, building location; (b) types of arrangement of educational infrastructure include movable property, immovable property, consumable movable property, non-consumable movable object; (c) supporting and inhibiting factors in the arrangement of facilities and infrastructure; (d) solutions in overcoming inhibiting factors in structuring facilities and infrastructure. (3) utilization of infrastructure facilities in Islamic Boarding School An-Nur II Malang; (a) use of learning tools; (b) use of visual aids; (c) the use of learning media; (d) supporting and inhibiting factors in the use of infrastructure; (e) solutions in overcoming inhibiting factors in the use of infrastructure. Abstrak: Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan penataan dan pemanfaatan sarana prasarana pembelajaran pendidikan formal dan nonformal. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian studi kasus. Data penelitian yang dilaksanakan di Pondok Pesantren An-Nur II Malang ini dikumpulkan menggunakan teknik wawancara, observasi, dan dokumentasi. Kemudian dianalisis melalui suatu proses interaktif melalui tahap reduksi, penyajian, dan verifikasi data. Adapun hasil penelitian ini yaitu: (1) jenis-jenis sarana prasarana di Pondok Pesantren An-Nur II Malang, (2) penataan sarana prasarana di Pondok Pesantren An-Nur II Malang; (a) prinsip-prinsip dalam penataan sarana prasarana pendidikan meliputi hubungan antar ruang, luas tanah, kerangka ruang, lokasi bangunan; (b) jenis-jenis penataan sarana prasarana pendidikan meliputi barang bergerak, barang tidak bergerak, barang bergerak habis pakai, barang bergerak tidak habis pakai; (c) faktor pendukung dan penghambat dalam penataan sarana prasarana; (d) solusi dalam mengatasi faktor penghambat dalam penataan sarana prasarana. (3) pemanfaatan sarana prasarana di Pondok Pesantren An-Nur II Malang; (a) pemanfaatan alat pelajaran; (b) pemanfaatan alat peraga; (c) pemanfaatan media pembelajaran; (d) faktor pendukung dan penghambat dalam pemanfaatan sarana prasarana; (e) solusi dalam mengatasi faktor penghambat dalam pemanfaatan sarana prasarana.